Advanced membrane technology and applications - Li, Norman N.; Fane, A. G.; Ho, W. S. Winston, 1943-; Matsuura, Takeshi, 1936- (Wiley, 2008)
Advanced membranes-from fundamentals and membrane chemistry to manufacturing and applications. A hands-on reference for practicing professionals. Advanced Membrane Technology and Applications covers the fundamental principles and theories of separation and purification by membranes, the important membrane processes and systems, and major industrial applications. It goes far beyond the basics to address the formulation and industrial manufacture of membranes and applications. This practical guide: includes coverage of all the major types of membranes: ultrafiltration; microfiltration; nanofiltration; reverse osmosis (including the recent high-flux and low-pressure membranes and anti-fouling membranes); membranes for gas separations; and membranes for fuel cell uses. Addresses six major topics: membranes and applications in water and wastewater; membranes for biotechnology and chemical/biomedical applications; gas separations; membrane contractors and reactors; environmental and energy applications; and membrane materials and characterization. Includes discussions of important strategic issues and the future of membrane technology.